2014
DOI: 10.1128/jvi.00538-14
|View full text |Cite
|
Sign up to set email alerts
|

Hypovirulence of the Phytopathogenic Fungus Botryosphaeria dothidea: Association with a Coinfecting Chrysovirus and a Partitivirus

Abstract: Botryosphaeria dothidea is an important pathogenic fungus causing fruit rot, leaf and stem ring spots and dieback, stem canker, stem death or stool mortality, and decline of pear trees. Seven double-stranded RNAs (dsRNAs; dsRNAs 1 to 7 with sizes of 3,654, 2,773, 2,597, 2,574, 1,823, 1,623, and 511 bp, respectively) were identified in an isolate of B. dothidea exhibiting attenuated growth and virulence and a sectoring phenotype. Characterization of the dsRNAs revealed that they belong to two dsRNA mycoviruses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 48 publications
(73 reference statements)
2
110
0
Order By: Relevance
“…At least two divergent clades of "chryso-like" viruses with either 3 or up to 5 genome segments have also been described, but not yet recognized as distinct taxa by the ICTV Urayama et al, 2010Urayama et al, , 2012Wang et al, 2014). One of the viruses associated with La France disease of A. bisporus (Van der Lende et al, 1996) appears to belong to one of these clades (Urayama et al, 2012), and indeed some other of these chryso-like viruses appear to alter colony morphology and reduce virulence of their host fungi, unlike recognized chrysoviruses.…”
Section: Chrysoviridae (Dsrna)mentioning
confidence: 92%
“…At least two divergent clades of "chryso-like" viruses with either 3 or up to 5 genome segments have also been described, but not yet recognized as distinct taxa by the ICTV Urayama et al, 2010Urayama et al, , 2012Wang et al, 2014). One of the viruses associated with La France disease of A. bisporus (Van der Lende et al, 1996) appears to belong to one of these clades (Urayama et al, 2012), and indeed some other of these chryso-like viruses appear to alter colony morphology and reduce virulence of their host fungi, unlike recognized chrysoviruses.…”
Section: Chrysoviridae (Dsrna)mentioning
confidence: 92%
“…Mycovirus infections can lead to induction of a cryptic state (asymptomatic), reduction of mycelial growth, change in the colour of the colony or even alteration of the specific structure formation (Rodríguez-García et al, 2014). The effects of mycoviruses on spore production and pathogenesis have also been widely reported (Kazmierczak et al, 1996;Wang et al, 2014, Zamora et al, 2016, indicating the potentially damaging effects of the viruses on plant health. Three different species of the genus Mitovirus that infect F. circinatum have recently been identified as putative members of Narnaviridae (genus Mitovirus) and designated Fusarium circinatum mitovirus 1, 2-1 and 2-2 (FcMV1, FcMV2-1 and FcMV2-2) (Martínez-Álvarez et al, 2014a;Vainio et al, 2015;Muñoz-Adalia et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…A protein with a molecular mass of 82 kDa was predicted from the 763-codon dsRNA3 ORF (ORF3; Figure 1B). A BLASTP search with the deduced amino acid sequence of ORF3 revealed that this protein had sequence homology to an 84-kDa protein encoded by PjCV1 (59% identity, 75% similarity), and to the putative capsid protein of Botryosphaeria dothidea chrysovirus (31% identity, 47% similarity) (Wang L. et al, 2014). Phylogenetic analysis of the putative AfuCV41362 capsid protein (ORF3) also suggested that AfuCV41362 belonged to Chrysoviridae cluster II ( Figure 2B and Supplementary Table S1B), as was indicated for ORF1.…”
Section: Nucleotide Sequences Of Dsrna and Phylogenetic Analysismentioning
confidence: 91%